Вільні коливання багатошарових циліндричних панелей з функціонально-градієнтними шарами - Курпа, Лідія Василівна; Шматко, Тетяна Валентинівна (Інститут прикладних проблем механіки і математики імені Я. С. Підстригача НАН України, 2019)
The R-functions theory and variational Ritz’s method is employed to research free vibrations of the laminated shallow shells with functionally graded layers. Mathematical formulation has used classical and Timoshenko’s theories. Created software is applied to investigate laminated FGM cylindrical shallow shells of the complex plan form and different boundary conditions. Effects of different geometrical and mechanical parameters on natural frequencies have been investigate
Free Vibration of Laminated Cylindrical Panels with Functionally Graded Layers
Keywords: багатошарові циліндричні панелі; функціонально-градієнтні шари; багатошарові пологі оболонки; теорії R-функцій